2006
DOI: 10.1038/sj.ijo.0803399
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of ghrelin is related to estimated insulin sensitivity in obese children

Abstract: Objective: To investigate whether ghrelin concentrations and their changes during weight loss in obese children are associated with parameters of glucose and insulin metabolism. Design: Total plasma ghrelin, insulin and glucose were measured during oral glucose tolerance testing before and after dietinduced weight loss over 6 weeks. Setting: In-patient rehabilitation program in a pediatric hospital. Participants: Twenty-three obese children (age 10-16 years) and 11 normal weight controls (age 10-15 years). Out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 38 publications
1
7
2
Order By: Relevance
“…Various studies have shown an increase of fasting plasma ghrelin levels after weight loss in obese children [8, 10, 13]. However, the amount of weight lost was substantially greater in these studies than in ours.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Various studies have shown an increase of fasting plasma ghrelin levels after weight loss in obese children [8, 10, 13]. However, the amount of weight lost was substantially greater in these studies than in ours.…”
Section: Discussioncontrasting
confidence: 65%
“…Generally, the plasma ghrelin concentration of obese children is lower in fasting condition [610], whereas the decline in response to glucose ingestion varies as a function of insulin sensitivity; the decline appears to be less profound in insulin resistant obese children [6, 11], although the data are equivocal [12]. Weight loss tends to normalize circulating ghrelin levels [8, 10, 13], although this is still a subject for debate [5, 14]. …”
Section: Introductionmentioning
confidence: 99%
“…In particular, Zou et al (2009) showed that ghrelin levels increase after only 1 month of a very strict weight reduction programme, including 3 h of aerobic exercises everyday and a daily calorie intake controlled at about 1,300-1,600 kcal. To the best of our knowledge, only one study reported an increase in ghrelin concentrations after weight loss in adolescents of similar age to our study (Krohn et al 2006). However, Krohn's study was conducted over a period of only 6 weeks in adolescents who did not have severe obesity (BMI z score of 2.85).…”
Section: Discussioncontrasting
confidence: 54%
“…Ghrelin levels in obese children are lower than in normal-weight children, and the levels are proportionate to the degree of insulin resistance [28], suggesting that ghrelin has a role in limiting food intake in the obese insulin-resistant individual. With weight loss, a rise in ghrelin occurs along with a decline in insulin and an increase in insulin sensitivity [29]. …”
Section: Regulatory Elements Of Linear Growth and Obesitymentioning
confidence: 99%